Genomic landscape of childhood acute lymphoblastic leukemia in Malaysia: insights from array-CGH - Azli Ismail; Fadly Ahid; Wong Nyuk Moi; Nor Rizan Kamaluddin; Ezalia Esa; Yuslina Mat Yusoff; Zahidah Abu Seman; Muhammad Asyraff Mohammed; Elizabeth George; Asmida Isa; Zubaidah Zakaria (Molecular Cytogenetics)
Abstract Background Acute lymphoblastic leukemia (ALL) is the most common childhood cancer, comprising approximately 25% of pediatric malignancies. Notably, chromosomal aberrations and genetic alterations play a central role in the pathogenesis of ALL, serving as critical diagnostic and prognostic markers. In this study, we use array-based comparative genomic hybridization (array-CGH) to explore the landscape of copy number variations (CNVs) and variants of uncertain significance (VUS) in 67 Malaysian childhood ALL patients with normal karyotype. Results A total of 36 pathogenic CNVs (26 gains, 10 losses) were identified in 19 (28.4%) patients which harbor genes related to the development of ALL. The genes include the MLLT3 (9p21.3), ETV6 (12p13.2), RUNX1 (21q22.12), ERG (21q22.2) and DMD (Xp21.1). On the other hand, a total of 46 variants of uncertain significance (VUS) was observed in 34 (50.7%) patients. Conclusions Our study indicates that array-CGH is able to identify and characterize the CNVs responsible for the pathogenesis of childhood ALL. However, further studies are required to determine the pathogenic implications of VUS in the development of childhood ALL.